UNICEF support to work on orphans in ESAR scaling up : strategies and urgent actions. - Eastern & Southern Africa Regional Workshop on Orphans & Vulnerable Children (2000 : Lusaka, Zambia); UNICEF Zambia; AID/Zambia. (Lusaka, Zambia : UNICEF : USAID, 2000)
Presents background documents and papers resulting from the regional gathering to address the needs of orphans and other vulnerable childre n living in eastern and southern Africa.
"Eastern & Southern Africa Regional Workshop on Orphans & Vulnerable Children"--Container.
Title from title screen.
Production level cataloging.
Includes bibliographical references.
System requirements: Adobe Acrobate Reader.
Keywords: Orphans -- Africa, Eastern -- Congresses; Orphans -- Africa, Southern -- Congresses; Children of AIDS patients -- Africa, Eastern -- Congresses; Children of AIDS patients -- Africa, Southern -- Congresses; Child welfare -- Africa, Eastern -- Congresses; Child welfare -- Africa, Southern -- Congresses